2004
DOI: 10.3846/16111699.2004.9636076
|View full text |Cite
|
Sign up to set email alerts
|

Youth Unemployment and Its Reduction Measures

Abstract: The efficient use of the labour force in post‐industrial society predetermines the competitiveness of the economy and encourages social development. In this context, youth unemployment is a particularly undesirable phenomenon, reducing the efficiency of youth labour force within the level of general labour, raising social costs, and restricting social development. The position of young people on the labour market depends on a number of social, economic and demographic factors, leading to the conclusion that yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
(1 reference statement)
1
3
0
1
Order By: Relevance
“…Secondly, the narratives show that the Namibian CLS seemed to be unskilled and unemployable, because their level of education was noticeably low. This finding is confirmed by other empirical studies which show that qualification and experience have an impact on the employment level of young people [37]. Furthermore, it is also expressed in empirical literature that unemployed youth are condemned to long-lasting depression should they fail to turn their theoretical knowledge into practical ability, gain skills and improve their professional competence [37].…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Secondly, the narratives show that the Namibian CLS seemed to be unskilled and unemployable, because their level of education was noticeably low. This finding is confirmed by other empirical studies which show that qualification and experience have an impact on the employment level of young people [37]. Furthermore, it is also expressed in empirical literature that unemployed youth are condemned to long-lasting depression should they fail to turn their theoretical knowledge into practical ability, gain skills and improve their professional competence [37].…”
Section: Discussionsupporting
confidence: 55%
“…This finding is confirmed by other empirical studies which show that qualification and experience have an impact on the employment level of young people [37]. Furthermore, it is also expressed in empirical literature that unemployed youth are condemned to long-lasting depression should they fail to turn their theoretical knowledge into practical ability, gain skills and improve their professional competence [37]. In light of the above, it is concluded that the unemployment situation of young people might result in depression and hopelessness.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The key area of interest explored could be factors influencing youth unemployment such as duration dependence (Flek et al , 2015; Cockx and Picchio, 2013; Raaum, 2009; García-Pérez and Muñoz-Bullón, 2005), skills (Cyron and Mehrotra, 2022; Groh et al , 2016), training (Šileika, 2004; Upward, 2002), income distribution (De Fraja et al , 2021; Singh et al , 2020), labour market (Liotti, 2022; Ylistö and Husu, 2021; Ranchhod and Daniels, 2021; Bradley and Crouchley, 2020), policies (Jumpah, 2020; Focacci, 2020), wage determination (Gabriel and Schmitz, 2020; Vasilescu and Begu, 2019), minimum wage (Fialová and Mysíková, 2021; Marimpi and Koning, 2018), labour supply (Holford, 2020; McTier and McGregor, 2018), education (Cyron and Mehrotra, 2022; Juárez et al , 2022; Krahn et al , 2015; Odoardi, 2020; Pompei and Selezneva, 2021; Meyer and Mncayi, 2021) and youth entrepreneurship (Munyuki and Jonah, 2021; Justina and Emmanuel, 2020; Jumpah, 2020; Ubogu, 2020).…”
Section: Results and Findingsmentioning
confidence: 99%
“…Proti, piedāvātās iespējas jauniešiem darba tirgū ir identiskas pieaugušo iespējām un otrādi. Veiksmīgas iekļaušanās rezultātā indivīdam netiek negatīvi ietekmēts materiālais stāvoklis un sociālā dzīve (Sileika et al, 2004).…”
Section: Jauniešu Sociālā Iekļaušanās Darba Tirgū/ Youth's Social Incunclassified